Pelatihan Masyarakat Kelurahan Rahmah Kota Lubuklinggau melalui Pelatihan Pembuatan Pupuk Organik dari Sekam Padi - Ansiska, Paisal; Latuserimala, Gerald; Sari, Indriati Meilina (Jurnal Pengabdian Arumbai, 2025)
The community of Kelurahan Rahmah, South Lubuklinggau I District, Lubuklinggau City, faces problems of heavy reliance on chemical fertilizers and underutilization of agricultural waste such as rice husks. This condition has led to declining soil fertility, rising production costs, and suboptimal use of local resources. This community service program aimed to enhance the community's capacity to process rice husks into environmentally friendly and economical organic fertilizer. The method used was Participatory Learning and Action (PLA), emphasizing participatory learning through hands-on practice and reflective discussion. The activities were carried out in stages, including socialization, technical training, fermentation practice, learning outcome evaluation, and follow-up mentoring. The results showed a significant increase in participants’ understanding and skills, particularly in the benefits and techniques of organic fertilizer production. Furthermore, the program encouraged community initiatives to produce fertilizer independently and form local processing groups. This transformation demonstrates that locally-based training can strengthen individual capacities while fostering collective awareness toward sustainable and self-reliant agriculture.